2015
DOI: 10.1039/c5nr01480h
|View full text |Cite
|
Sign up to set email alerts
|

The role of the interface in germanium quantum dots: when not only size matters for quantum confinement effects

Abstract: Quantum confinement (QC) typically assumes a sharp interface between a nanostructure and its environment, leading to an abrupt change in the potential for confined electrons and holes. When the interface is not ideally sharp and clean, significant deviations from the QC rule appear and other parameters beyond the nanostructure size play a considerable role. In this work we elucidate the role of the interface on QC in Ge quantum dots (QDs) synthesized by rf-magnetron sputtering or plasma enhanced chemical vapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…In a previous work, we observed that PECVD QDs exhibit a sharper interface with lower amount of Ge sub-oxide states in comparison with sputter samples, ensuring a stronger electron-hole confinement into Ge QDs of PECVD samples. 16 Since Tauc plot focuses the threshold energy range of absorption coefficient, which is affected by any midgap levels or bending induced by interface defects, the different behavior of our Tauc plots from those of Liu et al can be regarded as a consequence of the different growth technique used. In our case the Tauc plot is characterized by a unique linear region which extends over a wider spectral range (0.8 eV) with respect to the case of Ref.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous work, we observed that PECVD QDs exhibit a sharper interface with lower amount of Ge sub-oxide states in comparison with sputter samples, ensuring a stronger electron-hole confinement into Ge QDs of PECVD samples. 16 Since Tauc plot focuses the threshold energy range of absorption coefficient, which is affected by any midgap levels or bending induced by interface defects, the different behavior of our Tauc plots from those of Liu et al can be regarded as a consequence of the different growth technique used. In our case the Tauc plot is characterized by a unique linear region which extends over a wider spectral range (0.8 eV) with respect to the case of Ref.…”
Section: Resultsmentioning
confidence: 99%
“…16 Here, we briefly review the three models used for the extraction of optical bandgap in our samples [ Fig. 1(a)].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations